WHO BECOMES CONGRESSMAN? the impact of legal changes in the composition of the Chamber of Deputies (2002-2022) - Dantas, Humberto (2024)
Respecting the principle of annuality of electoral laws, political reforms have taken place in odd-numbered years initiated by the National Congress. In addition to these reforms, the active role of the judiciary in interpreting the current rules and formulating resolutions that alter the logic of the regulations guiding the elections is significant. Based on these aspects, the main objective of this article is to understand, based on information available in the databases of the Superior Electoral Court (TSE), the extent to which legal changes can alter the profile of candidacies and, additionally, how they impact who will be elected. In light of this effort, this work will start from the fundamental hypothesis that the profile of candidacies, to a greater extent, and of elected officials, to a lesser extent, change according to variations of an institutional-legal nature. This argument would be reinforced by the fact that variables that did not undergo legal changes between 2002 and 2022 do not undergo significant movements when considering candidacies and people elected to the position of federal deputy. Examples of variables that underwent changes or were directly impacted by the law are the total number of candidacies, the total number of parties, the average number of candidacies per party, female candidacies, candidacies of black individuals, and candidacies under coalitions. On the other hand, the total number of elected officials, the average age, the percentage of young individuals, education level, marital status, seeking re-election, and the birthplace of the candidates – the state where they were born – did not undergo changes.